PANCR, the PITX2 Adjacent Noncoding RNA, Is Expressed in Human Left Atria and Regulates PITX2c Expression. (January 2016) - Gore-Panter, Shamone R.; Hsu, Jeffrey; Barnard, John; Moravec, Christine S.; Van Wagoner, David R.; Chung, Mina K.; Smith, Jonathan D.
Abstract : Background—: Genome-wide studies reveal that genetic variants at chromosome 4q25 constitute the strongest locus associated with atrial fibrillation, the most frequent arrhythmia. However, the mechanisms underlying this association are unknown. Our goal is to find and characterize left atrial–expressed transcripts in the chromosome 4q25 atrial fibrillation risk locus that may play a role in atrial fibrillation pathogenesis. Methods and Results—: RNA sequencing performed on human left/right pairs identified an intergenic long noncoding RNA adjacent to the PITX2 gene, which we have named PANCR ( PITX2 adjacent noncoding RNA). In a human tissue screen, PANCR was expressed specifically in the left atria and eye and in no other chambers of the heart. The levels of PANCR and PITX2c RNAs were highly correlated in 233 human left atrial appendage samples. PANCR levels were not associated with either atrial rhythm status or the genotypes of the chromosome 4q25 atrial fibrillation risk variants. Both PANCR and PITX2c RNAs were induced early during differentiation of human embryonic stem cells into cardiomyocytes. Because long noncoding RNAs often control gene expression, we performed siRNA-mediated knockdown of PANCR, and this treatment repressed PITX2c expression and mimicked the effects of PITX2c knockdown on global mRNA and miRNA expression. Cell fractionation studies demonstrate that PANCR is primarily localized in the cytoplasm. Conclusions—: PANCR and PITX2c are coordinately expressed early during cardiomyocyte differentiation from stem cells. PANCR knockdown decreased PITX2c expression in differentiated cardiomyocytes, altering the transcriptome in a manner similar to PITX2c knockdown. Abstract : Supplemental Digital Content is available in the text.